Emergency orthodontic management of luxated permanent anterior teeth: A report of two cases showing role of orthodontist in multidisciplinary approach. - A C Mashru; S Goje (Journal of Integrated Health Sciences)
Traumatic luxation of permanent anterior teeth requires an appropriate emergency management and treatment plan. Very less data in literature is available regarding emergency orthodontic treatment in luxated teeth. Light orthodontic forces given in early period of trauma in selected cases can restore teeth in original position that can allow better periodontal healing. This article focuses on the principles which orthodontic specialist should consider while planning orthodontic movement of recently traumatized permanent teeth. Two cases are presented of emergency orthodontic treatment.